Mitigating data spoofing risks in Near Field Communication (NFC) read/write mode: an investigation into access control vulnerabilities and post-compromise recovery strategy - Megat Khalid, Puteri Shariza; Mohd Sani, Nor Fazlida (Little Lion Scientific, 2024)
The rapid growth of Near Field Communication (NFC) technology has facilitated its widespread adoption in everyday activities, particularly in cashless mobile payments and access control among urban dwellers. However, this convenience is accompanied by significant security risks, including data spoofing, relay attacks, and unauthorized data access. Despite advancements in NFC technology, a critical gap persists in securing communications, particularly at the end-user level, where awareness and preventive measures are insufficient. This research aims to address those gaps by focusing on end-user vulnerabilities and providing tailored solutions through the development of an NFC End-User specific security policy. The study's primary contribution lies in the development of an information security policy tailored specifically for NFC End-Users. This policy serves as a comprehensive guideline aimed at enhancing the security posture of individuals who utilize NFC-enabled devices. Unlike previous studies that primarily examine technical countermeasures, this work emphasizes the human factors by assessing user awareness and NFC secure practices. By developing an NFC security policy specifically for end users, the study aims to bridge the gap between technological safeguards and NFC End User behavior.